Outcomes With Venetoclax 50 mg, Hypomethylating Agents, and Voriconazole or Posaconazole in Acute Myeloid Leukemia - Kendall Diebold; Devan Parker; Sarah Worth; Manuel Espinoza‐Gutarra; Pankit Vachhani; Kimo Bachiashvili; Sravanti Rangaraju; Razan Mohty; Ravi Bhatia; Omer Jamy (eJHaem)
ABSTRACT Background Real‐world evidence for hypomethylating agent (HMA) + venetoclax 50 mg (VEN50) with voriconazole and posaconazole in acute myeloid leukemia (AML), is limited. Methods We evaluated outcomes of patients with newly‐diagnosed AML treated with HMA + VEN50 with either posaconazole (n = 23) or voriconazole (n = 95). Results We report that treatment with HMA + VEN50 with either azole elicits a response rate similar to that described in the VIALE‐A trial. Reducing the VEN dose to 50 mg with either strong CYP3A4 inhibitor did not compromise on the efficacy of the combination. Conclusion HMA + VEN50 with either posaconazole or voriconazole yields comparable responses to higher doses of VEN reported previously. Clinical trial registration The authors have confirmed clinical trial registration is not needed for this submission.